THE TEST OF STEEL AND REINFORCED CONCRETE COLUMNS, BOX-SECTION, AXIAL COMPRESSION - Halahuria, Ye. I. (Science and Transport Progress, 2007)
The article reresents the outcomes of testing the thin-walled steel and steel-concrete pillars of box-like section for central compression. In the course of experiment critical efforts of local stability loss of steel pillars and carrying ability of steel-concrete pillars were received.